Possibility of Using Fuel Cells and Hybrid Energy Systems for Energy Generation in Venizelio Hospital in Crete, Greece - Vourdoubas, John (Geography, Earth Science and Environment: Research Highlights Vol. 7, 2025)
Hospitals operate continuously all over the year and their specific energy consumption is high compared with other types of buildings. They mainly use fossil fuels and grid electricity while the use of renewable energy sources is limited so far. The possibility of using a) fuel cell and b) a hybrid energy system consisting of a fuel cell and solar photovoltaic modules to meet the heat and power demand in Venizelio Hospital located in Crete, Greece has been studied. The energy consumption in several sectors in Venizelio Hospital has been used in estimations. Our results indicated that a fuel cell with a capacity of 1,397 KW can meet the heat and power demand in the hospital producing excess heat at 2,451 MWhth per year. In the case of the hybrid energy system, a fuel cell with a capacity of 697.5 KW and a solar photovoltaic system with a nominal capacity of 1,629 KWp can meet the heat and power demand in the hospital. The total installation cost of the hybrid energy system, at 3,726,500 €, was lower than the installation cost of the fuel cell at 4,191,000 €. Our work indicates that the use of sustainable energy systems can replace the use of fossil fuels in hospitals reducing their carbon emissions and increasing their energy resilience. The results could be useful to policymakers, hospitals’ authorities and energy companies which design and install sustainable energy systems.